The Role of Scouting Activities in Strengthening Nationalism and Leadership Values in Schools - Nur Muhyi (Journal of Educational Research and Practice, 2025)
This study aims to describe the role of Scout activities in strengthening the values of nationalism and leadership at MTs Al Yakin. The background of this research stems from the phenomenon of declining patriotic spirit and leadership among students in the digital era, which necessitates a character education platform capable of fostering these values in a tangible way. The method used is a qualitative approach with descriptive research design. Data were collected through observation, in-depth interviews, and documentation involving Scout instructors, students, and the head of the madrasah. Data analysis was conducted interactively through the processes of reduction, presentation, and conclusion drawing. The results of the study indicate that Scout activities contribute significantly to instilling discipline, responsibility, cooperation, and a sense of nationalism. Additionally, activities such as flag ceremonies, marching drills, and community service help develop students’ leadership character. The main factors contributing to the success of these activities include the active role of the instructors, support from the madrasah, and consistent student participation. Thus, Scout activities at MTs Al Yakin can serve as a model for character development in nationalism and leadership for students at the madrasah level.